The Effect of the Constructive Learning Model on the Creative Thinking of the Second Secondary Students Scientific in Oman - Al-Shuaili, Ali; Alghafri, Ali (Jordan Journal of Educational Sciences, 2006)
This study aims at investigating the effect of using Constructivist learning model (CLM) in developing creative thinking at 11th grade level comparing with the traditional teaching method. The sample consisted of 117 students (male and female) in the experimental group, using the Constructivist learning model (CLM), whereas the control group consisted of 86 students and were taught according to the traditional method. After a seven-week experiment, a scientific creative thinking test was administered to all sample members. The finding revealed that there is a statistically significant difference in creative thinking between the experimental and control groups in favor of the experimental group. The study also showed that whereas male experiment students are better in fluency and flexibility, no significant differences were observed in originality. The research findings indicated the necessity of adopting the Constructivist model in science teaching in order to develop student,s creative thinking